Understanding Local Perspectives on Micro Hydropower Management in Galkot Municipality, Nepal: A Structural Equation Modeling Approach (The Journal of Economic Concerns, 2025)
This study examines the factors influencing local participation in micro hydropower (MHP) management in Galkot Municipality, Nepal, focusing on perceived benefits, knowledge, and attitudes. A quantitative research design was employed, collecting data from 285 MHP users in Ward No. 8 of Galkot Municipality through structured questionnaires. Structural Equation Modeling (SEM) was used to analyze the relationships between participatory behavior and key determinants, including perceived benefits, knowledge, and attitudes. The findings reveal a positive correlation between knowledge and participatory behavior (β = 0.42, p < 0.05), with informed communities more engaged in MHP governance and maintenance. Perceived benefits, such as economic diversification and energy security, also significantly influence participation (β = 0.41, p < 0.05). However, over 50% of respondents reported a lack of technical expertise, highlighting a critical gap in local capacity. The study emphasizes the need for systematic training programs and the establishment of local maintenance hubs to ensure MHP sustainability. Despite positive outcomes, 98.95% of respondents faced management challenges, with technical skills and government support identified as key areas for improvement. The study suggests that decentralized governance, technical skill development, and better coordination between stakeholders can enhance MHP system reliability. Additionally, the findings underscore the importance of economic necessity and service reliability in driving community involvement, rather than abstract environmental attitudes. Policy recommendations include strengthening local technical training, improving government incentives for MHP-based businesses, and establishing local repair networks. This study provides a valuable framework for optimizing MHP as a sustainable energy solution aligned with SDG 7.